The Dynamic Impact of Digital Economy on Carbon Emission Reduction: Evidence City-level Empirical Data in China - Li, Zhiguo; Wang, Jie (Journal of cleaner production, 2022)
The digital economy is of great significant for carbon emission reduction. To estimate the impact on carbon emissions of digital economy, this paper conducts nonlinear analysis with the combination of spatial DURBIN model (SDM) and panel threshold model (PTM). Moreover, this paper decomposes the carbon emissions reduction effect into direct part and spatial spillover part, further analyzes the action mechanism from the perspective of technology progress, energy use and industrial structure. The empirical results indicate that the digital economy and carbon emissions have inverted U-shaped relationship. Similarly, the spatial spillover effect of digital economy on carbon emissions is also inverted-U shape. The digital economy increases first and then reduces the carbon emissions. The robustness tests and endogenous analysis both support above conclusions. Compared with the indirect effect, the direct effect of digital economy on carbon emissions is significantly greater. Moreover, the long-term effect of digital economy on carbon emissions is greater than the short-term effect. The impact of digital economy on carbon emissions exists regional heterogeneity. Different from the eastern and central regions, the digital economy in western region promotes carbon emissions monotonically. The impact of digital economy on carbon emissions faces significant resource endowment thresholds, urban scale thresholds and innovative capability thresholds. The increase of energy use and non-green technology progress are the main paths to influence local carbon emissions in short term, while the green technology progress and industrial structure upgrade become dominant paths in long term. The active demonstration of industrial structure upgrade and technology spillovers drive the spillover effect of digital economy on carbon emissions in long term. This paper suggests that, the realization of carbon peak and carbon neutral needs to strengthen the digital economy and promote the regional cooperation in environmental governance. The green integration of digital economy and traditional industries is of great significant for carbon emission reduction.